2021
DOI: 10.3390/pharmaceutics13020269
|View full text |Cite
|
Sign up to set email alerts
|

Surface Coating with Hyaluronic Acid-Gelatin-Crosslinked Hydrogel on Gelatin-Conjugated Poly(dimethylsiloxane) for Implantable Medical Device-Induced Fibrosis

Abstract: Polydimethylsiloxane (PDMS) is a biocompatible polymer that has been applied in many fields. However, the surface hydrophobicity of PDMS can limit successful implementation, and this must be reduced by surface modification to improve biocompatibility. In this study, we modified the PDMS surface with a hydrogel and investigated the effect of this on hydrophilicity, bacterial adhesion, cell viability, immune response, and biocompatibility of PDMS. Hydrogels were created from hyaluronic acid and gelatin using a S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…Coating the implant surface with ECM molecules that endorse the integration of the implants with the host tissue boosts biocompatibility by dampening the proinflammatory signaling cascades. 229 Negatively charged glycosaminoglycans (GAGs) are one of the critical components of ECM. Covalent attachment of the GAGs onto the implantable devices showed enhanced anti-inflammatory effect due to regulatory T cell activation.…”
Section: Protein/ecm Molecule Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Coating the implant surface with ECM molecules that endorse the integration of the implants with the host tissue boosts biocompatibility by dampening the proinflammatory signaling cascades. 229 Negatively charged glycosaminoglycans (GAGs) are one of the critical components of ECM. Covalent attachment of the GAGs onto the implantable devices showed enhanced anti-inflammatory effect due to regulatory T cell activation.…”
Section: Protein/ecm Molecule Coatingmentioning
confidence: 99%
“…231 tissue while attenuating the fibrotic tissue formation in a rat model for 2 months. 229 Blood-contacting devices such as cardiovascular stents have limited long-term clinical success due to the in-stent restenosis, a series of events including thrombosis, platelet aggregation on the metal stent, and reduced re-endothelialization. 248 Heparin, the most clinically used anticoagulant molecule, has been known to prevent the early stage of thrombosis.…”
Section: Protein/ecm Molecule Coatingmentioning
confidence: 99%
“…These results were consistent with those of previous studies, which showed that hydrophilic surfaces were better at preventing protein adsorption than hydrophobic surfaces. 21 , 50 , 59 , 60 Figure 2d shows cell cytotoxicity results using the 3‐[4,5‐dimethylthiazol‐2‐yl]‐2,5‐diphenyltetrazolium bromide (MTT) assay. The PDMS and IA‐PDMS samples showed significantly lower absorbance than cells on a plate at Days 1, 3, and 7 ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Recognising that the hydrophobic surface of silicone elastomer breast implants encourages absorption of proteins and bacterial adhesion, Joo et al described a method to introduce surface hydrophilicity by chemical modification using a crosslinked hydrogel containing hyaluronic acid and gelatin. 168 As with any surface-grafting strategy, introduction of such a method into an industrial manufacturing process would be complex and lead to increased costs, at least compared to current manufacturing methods; the surface modification step would need to be completed after manufacture of the breast implant shell, and would involve exposing the shell to oxygen plasma treatment, reaction of the resulting silanol groups with a silane, and then final conjugation of the hydrogel system. Nonetheless, the data indicate that the method is useful in improving hydrophilicity and biocompatibility, effective in reducing bacterial adhesion following implantation in mice, but only moderately effective at reducing capsule thickness.…”
Section: Modification Of Implant Surface With Grafted Drug Substancesmentioning
confidence: 99%